Analisis Pemahaman Hukum Kekekalan Bilangan Berdasarkan Teori Perkembangan Kognitif Piaget - Hasan, Nurfadillah; Mahmudah, Ashfa Nurul; Aulia, Tatu Helsa; Nurmalasari, Ulfi; Janah, Zahra Wardatul; Putri, Hafiziani Eka (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to evaluate the level of understanding of the concept of conservation of numbers in students of PAUD age (six years) and 2nd grade elementary school (nine years) based on Jean Piaget's cognitive development theory. A descriptive qualitative approach was used with direct observation techniques and semi-structured interviews, as well as a number conservation test using marbles, coins, and round paper of different sizes. The subjects of the study consisted of four children: two six-year-old children at RA Salafiyah and two nine year-old children at SDN 5 Nagrikaler, Purwakarta Regency. The results showed that six-year-old children had understood the principle of conservation of numbers and realized that the number of objects remained the same even though the arrangement and size changed according to Piaget's concrete operational stages. In contrast, nine-year-old students had not fully mastered the concept, they were still influenced by the visual perception of size and arrangement. Factors of learning motivation, additional experiences (tutoring and family support), and individual interests played an important role in this difference in understanding. The findings confirm that chronological age is not the only determinant of cognitive development, so that mathematics learning strategies need to be adjusted to the characteristics of students' motivation and learning experiences.